Measuring the Development of Islamic Education in Indonesia - Wiratama, Budhi Fatanza; Safitri, Zasya (Muslim Education Review, 2023)
Islam holds an important position in various human development processes in Indonesia, one of them is in the education sector. The Indonesian government through the Ministry of Religious Affairs established madrasas and Islamic Higher Education as an Islamic-based formal educational institution. Through logic and science, education is the way for humans to develop equally regardless of their gender. Herein lies the role of Islamic-based education to uphold this anti-discrimination principle. This research has the aim of conducting a composite index, namely the Islamic Education Development Index (IEDI) to describe the condition of Islamic education development at the provincial level in Indonesia. In addition, statistical modeling is carried out to see the influence of Islamic education on the Gender Development Index (GDI). The IEDI is a composite index consisting of five indicators including infrastructure accessibility, teaching competence, institutional ranking, outcomes, and quality of the learning process. Based on the research results, the average IEDI score of provinces in Indonesia is 45.13 for the period 2019. The best IEDI score by province is Yogyakarta, reaching a score of 55.00, and the lowest is North Kalimantan, which is only 35.90. Based on modeling results, it was also found that the IEDI has a significant effect on increasing the GDI at the confidence interval (CI) up to 95 percent. Governments can begin to pay more attention to Islamic-based education to optimize this influence.